Continental patterns in the diet of a top predator: Australia's dingo. (17th October 2018) - Doherty, Tim S.; Davis, Naomi E.; Dickman, Chris R.; Forsyth, David M.; Letnic, Mike; Nimmo, Dale G.; Palmer, Russell; Ritchie, Euan G.; Benshemesh, Joe; Edwards, Glenn; Lawrence, Jenny; Lumsden, Lindy; et al.
Abstract: Conserving large carnivores is controversial because they can threaten wildlife, human safety, and livestock production. Since large carnivores often have large ranges, effective management requires knowledge of how their ecology and functional roles vary biogeographically. We examine continental‐scale patterns in the diet of the dingo – Australia's largest terrestrial mammalian predator. We describe and quantify how dingo dietary composition and diversity vary with environmental productivity and across five bioclimatic zones: arid, semi‐arid, tropical, sub‐tropical, and temperate. Based on 73 published and unpublished data sets from throughout the continent, we used multivariate linear modelling to assess regional trends in the occurrence of nine food groups (arthropods, birds, reptiles, European rabbits Oryctolagus cuniculus, medium‐sized [25–125 kg] and large [169–825 kg] exotic ungulates [including livestock], and other small [<0.5 kg], medium‐sized [0.5–6.9 kg] and large [≥7 kg] mammals) in dingo diets. We also assessed regional patterns in the dietary occurrence of livestock and the relationship between dietary occurrence of rabbits and small, medium‐sized and large mammals. Dingoes eat at least 229 vertebrate species (66% mammals, 22% birds, 11% reptiles, and 1% other taxa). Dietary composition varied across bioclimatic zones, with dingo diets in the arid and semi‐arid zones (low‐productivity sites) having the highest occurrence of arthropods, reptiles, birds, and rabbits. Medium‐sized mammals occurred most frequently in temperate and sub‐tropical zone diets (high‐productivity sites), large mammals least in the arid and sub‐tropical zones, and livestock most in the arid and tropical zones. The frequency of rabbits in diets was negatively correlated with that of medium‐sized, but not small or large mammals. Dingoes have a flexible and generalist diet that differs among bioclimatic zones and with environmental productivity in Australia. Future research should focus on examining how dingo diets are affected by local prey availability and human‐induced changes to prey communities. Abstract :